Socrates on Egoism. Does he say we should be virtuous and egoists? (2013)
In this paper I address the issue whether Socratic eudaimonia entails egoism. It is, whether according to Socrates’ view a man who acts having his happiness as final criteria for his acts is an egoist. This view seems to be in contradiction with what we c